2020
DOI: 10.1088/1757-899x/830/2/022030
|View full text |Cite
|
Sign up to set email alerts
|

Road infrastructure asset management strategy and its impact on the environment

Abstract: The development of the economic sector is determined by services to the public through reforms that aim to place public satisfaction through the management of road infrastructure assets. Some research on road infrastructure assets still requires a deepening of studies related to the delivery of public services related to asset management systems. The purpose of this study is to find an appropriate road infrastructure asset management strategy through an integrated asset management system and asset management p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In [15], an evolutionary analysis of the impact of a three-dimensional model of technology, market, and policy on the development of the automobile industry on new energy sources in China is conducted. The comparison study [24] substantiates that the emission reduction of hydrocarbon fuel products is most effectively achieved with a reasonable investment in road transport and transport infrastructure. Based on the game model, it was shown that a certain state policy, for example, in taxi services, determines a winning strategy for motor vehicles based on CNG [23].…”
Section: Introductionsupporting
confidence: 55%
“…In [15], an evolutionary analysis of the impact of a three-dimensional model of technology, market, and policy on the development of the automobile industry on new energy sources in China is conducted. The comparison study [24] substantiates that the emission reduction of hydrocarbon fuel products is most effectively achieved with a reasonable investment in road transport and transport infrastructure. Based on the game model, it was shown that a certain state policy, for example, in taxi services, determines a winning strategy for motor vehicles based on CNG [23].…”
Section: Introductionsupporting
confidence: 55%